2022
DOI: 10.1371/journal.pwat.0000033
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of temperature and hydraulic regime on discolouration and biofilm fouling in drinking water distribution systems

Abstract: Discolouration is the greatest cause of customer dissatisfaction with drinking water quality, potentially masking other failures, including microbial issues, which can impact public health and well-being. The theorised association between biofilms (complex microbial communities) and discolouration within drinking water distribution systems (DWDS) was explored, whilst studying the impact and interactions of seasonal temperature variations and hydraulic regime. Transferability of findings to operational DWDS was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
(79 reference statements)
0
9
0
Order By: Relevance
“…This supports the theory that material accumulation is a biologically mediated process as higher water temperature is associated with increased microbiological and therefore biofilm activity. 27,29 It would therefore be expected to observe more material accumulating during warmer periods, as also seen by Blokker and Schaap. 9 Higher material accumulation in the warmer seasons however could also be linked to the higher treated water organic and inorganic metal concentrations loadings, as shown in Fig.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…This supports the theory that material accumulation is a biologically mediated process as higher water temperature is associated with increased microbiological and therefore biofilm activity. 27,29 It would therefore be expected to observe more material accumulating during warmer periods, as also seen by Blokker and Schaap. 9 Higher material accumulation in the warmer seasons however could also be linked to the higher treated water organic and inorganic metal concentrations loadings, as shown in Fig.…”
Section: Discussionmentioning
confidence: 61%
“…23–25 Material accumulation, and hence discolouration risk, have been reported to be influenced by daily hydraulic conditions, 2,11,26 pipe material 15 and water temperature. 16,27 While some studies have showed temperature and microbial influence on discolouration risk, 16,27–29 the variation of accumulation processes and rates seasonally has not yet been rigorously demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Hydraulics have been repeatedly documented to influence biofilm volume, EPS composition, cohesive strength, morphology, growth rates and community composition. [39][40][41][42][43][44][45] Biofilm-hydraulic trends do not converge in the literature, with some studies reporting increased density and adhesion/ cohesion with increased shear stress or velocity 41,45 and others observing the opposite, that adhesion/cohesion is reduced under greater ranges of velocity. 42,44 The range of impacts of hydraulics on biofilm characteristics is likely due to different operating conditions and sampling procedures.…”
Section: And S3 †)mentioning
confidence: 99%
“…Sometimes, flushing can be applied in conjunction with high concentrations of disinfectant (i.e., hyperchlorination) for more effective system cleaning, especially after pipes burst and are repaired (Chaves Simões and Simões, 2013;van Bel et al, 2019). These cleaning methods are known not to completely eliminate biofilm in the networks but remove weaker attached material that is commonly associated with the greatest risk to water quality, including discoloration (Douterelo et al, 2013;Fish, 2013). It is also known that the microorganisms remaining attached to the pipe wall can contribute to biofilm regrowth (Douterelo et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%